2005
DOI: 10.1021/la050593x
|View full text |Cite
|
Sign up to set email alerts
|

Fe(CO)5 Thin Films Adsorbed on Au(111) and on Self-Assembled Organic Monolayers:  I. Structure

Abstract: The adsorption of Fe(CO)(5) onto Au(111)/mica and C(4), C(8), C(12), and C(16) SAMs/Au(111)/mica surfaces has been studied using infrared spectroscopy to elucidate the coverage-dependent structures of these films and the intermolecular couplings that determine the form of the spectra. For all substrates, the first layer is composed of molecules physisorbed with one axial and two equatorial carbonyl groups directed toward the substrate; subsequent layers are preferentially oriented with the C(3) molecular axis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 69 publications
2
16
0
Order By: Relevance
“…This type of phenomena is prevalent for strong IR adsorbers, such as the symmetric stretch of metal carbonyls. 39,52,53 Consistent with this argument, the frequency observed at the lowest W(CO) 6 coverages, in the present study where there are no intermolecular effects, is closest to the peak position observed for W(CO) 6 in other isolated situations (e.g. gas phase or inert gas matrices).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…This type of phenomena is prevalent for strong IR adsorbers, such as the symmetric stretch of metal carbonyls. 39,52,53 Consistent with this argument, the frequency observed at the lowest W(CO) 6 coverages, in the present study where there are no intermolecular effects, is closest to the peak position observed for W(CO) 6 in other isolated situations (e.g. gas phase or inert gas matrices).…”
Section: Resultssupporting
confidence: 90%
“…Based on the studies of McCash et al 51,52 as well as Rowntree et al, who conducted a detailed RAIRS study of the structure of Fe(CO) 5 on Au(111), 39 we can assign the lower frequency band to a disordered monolayer state of W(CO) 6 and the higher frequency peak that appears at higher W(CO) 6 coverages to a more ordered multilayer state representative of W(CO) 6 in the solid phase. In these previous RAIRS studies the metal carbonyls were diluted in inert gas matrices to show that the blue shifts in frequencies that occur within each one of the two bands as the W(CO) 6 coverage increases are due to repulsive intermolecular dipole-dipole coupling interactions caused by the simultaneous oscillations of the surrounding dipole moments.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, current continuum models restrict their range of applicability to Langmuir adsorption, where a maximum of one monolayer can be adsorbed [ 1 ]. Multilayer adsorption is, however, common in standard vacuum science studies, usually conducted at low temperatures [ 33 36 ], in cryogenic FEBID [ 37 ] and at higher temperatures for precursors with low volatility [ 1 ]. The breakage of the Langmuir model is also common for low adsorbate concentrations on heterogeneous substrates [ 38 ].…”
Section: Introductionmentioning
confidence: 99%